Optimal number and discharge rate of emitters for coconut palm in sandy loam soil - PRIYA G. NAIR; Er. P. Suseela (Guide) (Tavanur 2000 Kelappaji College of Agricultural Engineering and Technology)
Optimal number and discharge rate of emitters for coconut palm in sandy loam soil
Optimal number and discharge rate of emitters for coconut palm in sandy loam soil